2014
DOI: 10.5334/pb.ag
|View full text |Cite
|
Sign up to set email alerts
|

Mental imagery during daily life: Psychometric evaluation of the Spontaneous Use of Imagery Scale (SUIS)

Abstract: The Spontaneous Use of Imagery Scale (SUIS) is used to measure the tendency to use visual mental imagery in daily life. Its psychometric properties were evaluated in three independent samples (total N = 1297). We evaluated the internal consistency and test-retest reliability of the questionnaire. We also examined the structure of the items using exploratory and confirmatory factor analysis. Moreover, correlations with other imagery questionnaires provided evidence about convergent validity. The SUIS had accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 38 publications
(52 reference statements)
9
71
3
1
Order By: Relevance
“…The SUIS has good internal consistency of 0.76 (Nelis et al, 2014), and was comparable in the current study at 0.84. recognition scenarios task was used to assess interpretation biases pre-and post-training. Pretraining, participants were presented with ten ambiguous scenario descriptions that were paired with a title.…”
Section: Spontaneous Use Of Imagery Scale (Suis)supporting
confidence: 51%
“…The SUIS has good internal consistency of 0.76 (Nelis et al, 2014), and was comparable in the current study at 0.84. recognition scenarios task was used to assess interpretation biases pre-and post-training. Pretraining, participants were presented with ten ambiguous scenario descriptions that were paired with a title.…”
Section: Spontaneous Use Of Imagery Scale (Suis)supporting
confidence: 51%
“…The spontaneous use of mental imagery in everyday life was assessed via the Spontaneous Use of Imagery Scale (SUIS) and two Visual Analogue Scales (VASs) . The SUIS is a 12‐item self‐report scale measuring the use of non‐emotional mental imagery in daily life (e.g., If I am looking for new furniture in a store, I always visualize what the furniture would look like in particular places in my home .).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have investigated only selected stages of imagery‐related processing, with evidence of deficits in cognitive tasks of imagery generation and manipulation in depressed individuals and imagery generation in anxious individuals . The subjective domains relate to spontaneous imagery use, the presence of imagery‐related interpretation biases and emotional mental imagery and the phenomenological characteristics of mental imagery in different affective states …”
Section: Introductionmentioning
confidence: 99%
“…While the VVIQ is a subjective measure, Cui et al (2007) showed that it correlated with individual differences in activity in primary visual cortex during mental imagery tasks (r = .73), illustrating its construct validity. The measure has been previously used in online studies with good psychometric properties (e.g., Nelis, Holmes, Griffith, & Raes, 2014), suggesting there are no reliability concerns in administering the measure online. Cronbach's alpha was .89 in this study.…”
Section: Procedures and Measuresmentioning
confidence: 99%